1992
DOI: 10.1002/j.1460-2075.1992.tb05426.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3′-kinase is activated by association with IRS-1 during insulin stimulation.

Abstract: IRS‐1 undergoes rapid tyrosine phosphorylation during insulin stimulation and forms a stable complex containing the 85 kDa subunit (p85) of the phosphatidylinositol (PtdIns) 3′‐kinase, but p85 is not tyrosyl phosphorylated. IRS‐1 contains nine tyrosine phosphorylation sites in YXXM (Tyr‐Xxx‐Xxx‐Met) motifs. Formation of the IRS‐1‐PtdIns 3′‐kinase complex in vitro is inhibited by synthetic peptides containing phosphorylated YXXM motifs, suggesting that the binding of PtdIns 3′‐kinase to IRS‐1 is mediated throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
592
3
6

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 990 publications
(634 citation statements)
references
References 51 publications
23
592
3
6
Order By: Relevance
“…This structure is very similar to the one exhibited by the Insulin Receptor Substrate-1 (IRS-1), a p185 kDa prominent cytoplasmic substrate of the InsulinReceptor (IR), Insulin like Growth Factor-Receptor (IGF-1R) and several cytokine receptors including interleukin (IL)-4 and IL-13 receptors (Schnyder et al, 1996). IRS-1 was found to form multimolecular complexes with the regulatory subunit of PI 3-kinase (Backer et al, 1993), SH-PTP2 (Kuhne et al, 1994), Nck (Lee et al, 1993), Grb2 (Pruett et al, 1995) and Fyn (Sun et al, 1996). Even though c-Cbl has also been shown to associate with a variety of transduction proteins, data supporting the formation of multimolecular complexes analogous to those observed with IRS-1 remained elusive.…”
Section: Discussionmentioning
confidence: 61%
“…This structure is very similar to the one exhibited by the Insulin Receptor Substrate-1 (IRS-1), a p185 kDa prominent cytoplasmic substrate of the InsulinReceptor (IR), Insulin like Growth Factor-Receptor (IGF-1R) and several cytokine receptors including interleukin (IL)-4 and IL-13 receptors (Schnyder et al, 1996). IRS-1 was found to form multimolecular complexes with the regulatory subunit of PI 3-kinase (Backer et al, 1993), SH-PTP2 (Kuhne et al, 1994), Nck (Lee et al, 1993), Grb2 (Pruett et al, 1995) and Fyn (Sun et al, 1996). Even though c-Cbl has also been shown to associate with a variety of transduction proteins, data supporting the formation of multimolecular complexes analogous to those observed with IRS-1 remained elusive.…”
Section: Discussionmentioning
confidence: 61%
“…Specifically, BVR has been suggested to act as a kinase for insulin receptor substrate (IRS) [20]. Since the activation of Akt is initiated by docking of PI3 kinase to phosphorylated IRS via its p85α subunit [43], it is plausible that BVR, by activating IRS phosphorylation, initiates PI3 kinase docking and subsequent activation of the Akt pathway. Additionally, BVR also has a sequence motif similar to IRS [20] which is required for SH2 binding proteins such as p85, suggesting that the enzyme, itself, may serve as a docking site for PI3 kinase and subsequent activation of the pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In favour with this hypothesis, high PI3K activity associated with Ras and phosphotyrosine containing proteins was observed both in transformed cell lines and primary tumours (not shown). Both mechanisms lead to an increase in intrinsic enzymatic activity (Backer et al, 1992;Rodriguez-Viciana et al, 1996) and therefore may take part of the observed PI3K deregulation. Previous reports attributed a function for PI3Ks in cell division, survival, cell dedi erentiation (Phillips et al, 1998), migration and tumour invasion (Kobayashi et al, 1999;Shaw et al, 1997).…”
Section: Discussionmentioning
confidence: 99%